Using Motion-Capture to Establish the Efficacy of Surgical vs Non-Surgical Treatment of Clubfoot via Gait Analysis: A Systematic Review - Jacob Veliky BS; Aedan Hanna; Julia Nguyen BS; Jae Hoon Choi; Dhvani Shihora; Aleksandra McGrath; Folorunsho Edobor-Osula MD; Neil Kaushal; Alice Chu (Foot & Ankle Orthopaedics, 2022)
Category: Midfoot/Forefoot; Hindfoot; Other Introduction/Purpose: Clubfoot is a common disorder among newborns which impedes the patient's ability to walk normally if left untreated. There exists a debate on the most effective way to treat clubfoot; surgical methods, such as the posteromedial release and percutaneous achilles tenotomy, are preferred by some surgeons, while non-operative methods, including the Ponseti and French methods, are favored by others. One technique that has recently gained traction in the assessment of clubfoot treatment is gait analysis, which uses motion-capture technology to record several parameters of movement in patients with clubfoot to assess their function compared to healthy controls. In this study, we aim to analyze existing literature on motion- capture data to compare ankle power and walking speed in clubfoot patients who were treated operatively and non-operatively. Methods: A comprehensive search was conducted of PubMed, CINAHL, Web of Science, and Cochrane publications to identify all available literature on clubfoot. Using PRISMA guidelines and a string of MeSH terms, all available articles on clubfoot were identified. The literature was then screened so that only articles containing more than three human subjects on pediatric patients with detailed gait analysis outcomes were selected. Initially, 26 papers on gait analysis were included, from which nine were excluded due to repeated papers and those on patients with secondary clubfoot. From the remaining papers, 11 had relevant outcome measures which were extracted including patient number, age, ankle power, and walking speed. All steps of screening were screened so that two authors independently verified that each paper met criteria for inclusion. Results: Initial search revealed 6469 articles. After review, 11 remained. Average age of surgical patients was 8.35, and the average age was 5.5 for non-surgical patients. In surgically treated clubfeet, the average ankle power was 1.591 W/kg (stdev = 0.702W/kg). In non-surgically treated clubfeet, the average ankle power was 2.334 W/kg (stdev = 0.792W/kg). Analysis via t-test revealed no significant difference between ankle power in surgically treated and non-surgically treated clubfeet (p = .125). When assessing walking speed, the average among surgically treated clubfeet was 0.721m/s (stdev = 0.136m/s), whereas in non- operatively treated clubfeet, the average was 0.99m/s (stdev = 0.212m/s). This difference was not statistically significant (t-test, p=0.072). Conclusion: This systematic review of motion-capture data revealed that there is no significant difference in ankle power or walking speed between surgically treated and non-surgically treated clubfeet. This may have been affected by the age difference between the cohorts. The need for further research in this area is evident due to the low volume of material on gait analysis despite the detailed metrics provided by this method.